Translational learnings from Australia: How SPAA plays a role in increasing the adoption of precision agriculture. (1st June 2017) - Dimos, N.; Schaefer, R.; Leonard, E.; Koch, J.
Abstract : The Society of Precision Agriculture Australia Inc. (SPAA) is recognised as a leading, grower driven farming group in Australia. As an organisation it provides programs and services to its members and wider industry to promote the development and adoption of Precision Agriculture (PA) technologies as a means of enhancing the profitability and sustainability of agricultural production systems. This is achieved through publishing Australia's only PA-dedicated magazine, delivering field days, seminars and conducting on-farm PA demonstrations and experiments. SPAA provides farmers with an independent source of advice on new concepts and equipment. The grains industry was the springboard for initial adoption, with winegrapes, horticulture and the sugar industry the focus sectors for further expansion. The purpose of this paper is to share the SPAA experience with a view to assisting the development of similar organisations in other countries